Instructional Leadership and Professional Learning Community Engagement in Relation to Teacher Competence in Public Elementary Schools of Rizal District - Palazo, Edelyne (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between instructional leadership, professional learning community (PLC) engagement, and teacher competence among public elementary school teachers in Rizal District, Occidental Mindoro. Anchored on instructional leadership frameworks and the Philippine Professional Standards for Teachers (PPST), the study employed a quantitative descriptive-correlational research design to determine the levels of the variables and their statistical relationships without establishing causality. Data were collected using a validated survey questionnaire administered to teachers across selected public elementary schools, and analyzed through descriptive statistics, Pearson correlation, and regression analysis. Findings revealed that instructional leadership, PLC engagement, and teacher competence were all rated at high levels. Significant positive relationships were found between teacher competence and the instructional leadership dimensions of managing the instructional program and promoting a positive school learning climate, while defining the school mission showed no significant relationship. All PLC dimensions were significantly associated with teacher competence, with supportive conditions emerging as the strongest predictor. Regression results further indicated that a positive school learning climate and supportive conditions within PLCs were the most influential factors in enhancing teacher competence. The study concludes that effective instructional leadership and collaborative professional environments are critical in strengthening teachers’ professional capabilities and instructional quality, and recommends sustaining supportive, collaborative, and growth-oriented school conditions. This study supports Sustainable Development Goal 4 (Quality Education) by emphasizing the importance of teacher development and effective school leadership in improving educational outcomes. It also contributes to sustainability by strengthening institutional practices that promote continuous professional growth, collaborative culture, and improved instructional quality within public elementary schools.